Aid Programs Integration: Case Study of Alzaatri Refugee Camp in Jordan - Jaber, Rola; Nashwan, Ayat (Dirasat: Human and Social Sciences, 2022)
This research explores the complexity of the humanitarian aid process as it involves multiple actors. The research depends on the idea that INGOs is one of the most powerful actors in Humanitarian Aid, with more influence on the aid programs they execute and also the influence on other actors’ roles. Therefore, the role they play is very important not only to deliver aid, rather to how they deliver it, and how the delivery mechanism they adopt can affect the relationships between INGOs and their partners. In addition, the research takes the position of participatory approach to examine the INGOs performance. The research pinpoints the cross-implementing programs, through outlines the strategies and mechanism they adopt in Alzaatari camp as a practical case. The research states the aid programs that INGOs select and run in the camp, and how they execute it. The study covers two main aid programs run in the camp WASH and CFW, as these programs related to different live aspects, and need different mechanism to execute. Finally, the research studies the level of the integration among humanitarian aid process.